Constraints Facing Poultry Producers in Iraq - bassim haleem kshash; hayat oda (Journal of Agricultural Extension, 2019)
There is a decrease in poultry production in Iraq. The study was conducted in Babylon Province, Iraq, to identify constraints facing broilers breeders. One hundred poultry producers were randomly selected. A list of 4 categories facing poultry producers: production, financial, marketing and institutional, covering 24 constraints was prepared. Above half of poultry producers indicated there was a high level of constraint facing them. Production, financial, and marketing categories had high effect on producers. High cost of  feed, competition from imported birds  ,market/price fluctuation, high cost of  energy, inappropriate environmental conditions , continuous outages electricity, high cost of drug and vaccines , high mortality rate , competition of  birds from other province ,lack of quality day old chicks from local hatcheries, high losses of feed, lake of capital , poor extension service , production halls not utilize at full operating capacity, lack of quality feeds, and disease attack were the most effected constraints.Negative significant relationships between years of experience in poultry production, number of chickens sets/ year, and training attendance with overall constraint score. There were differences between constraints effect depending on years of experience, number of chickens sets/ year, and training attendance. Challenges facing poultry producers can be addressed through active extension services.